2000
DOI: 10.1002/1098-2744(200008)28:4<203::aid-mc3>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of wild-type p53 protein for maintenance of chromosomal integrity

Abstract: Chromosomal double‐strand breaks (DSBs) occurring in mammalian cells can initiate genomic instability, and their misrepairs result in chromosomal deletion, amplification, and translocation, common findings in human tumors. The tumor‐suppressor protein p53 is involved in maintaining genomic stability. In this study, we demonstrate that the deficiency of wild‐type p53 protein may allow unrepaired DSBs to initiate chromosomal instability. The human lymphoblastoid cell line TK6‐E6 was established by transfection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 52 publications
2
14
1
2
Order By: Relevance
“…An extensive characterization of the positive correlation between reduced levels of normal TP53 and several instability end points has been demonstrated in human cell lines (Honma et al, 1997(Honma et al, , 2000Schwartz et al, 2001;Leger and Drobetsky, 2002). Further work using unstable clones from the human chromosome 4 hamster-hybrid system (GM10115) has shown that the radiosensitive phenotype was related to the efficiency of DNA repair (Limoli et al, 2001), supporting earlier results in GADD45 À/À mice.…”
Section: Introductionsupporting
confidence: 70%
“…An extensive characterization of the positive correlation between reduced levels of normal TP53 and several instability end points has been demonstrated in human cell lines (Honma et al, 1997(Honma et al, , 2000Schwartz et al, 2001;Leger and Drobetsky, 2002). Further work using unstable clones from the human chromosome 4 hamster-hybrid system (GM10115) has shown that the radiosensitive phenotype was related to the efficiency of DNA repair (Limoli et al, 2001), supporting earlier results in GADD45 À/À mice.…”
Section: Introductionsupporting
confidence: 70%
“…In addition, p53 plays an important role in maintaining genomic stability (Harvey et al, 1993;Albrechtsen et al, 1999;Janus et al, 1999;Burt et al, 2000;Honma et al, 2000;Overholtzer et al, 2003). Since we demonstrated that LMP1 could repress DNA repair in both p53-wild-type and p53-deficient human epithelial cells (Liu et al, 2004), it seems that LMP1 may repress DNA repair in a p53-independent manner.…”
Section: Discussionmentioning
confidence: 82%
“…p53 is critical for maintaining integrity of the genome (34,35), and hence decreased p53 in suspended cells could cause genetic instability. Treatment with radiation or chemotherapy then could lead to accumulation of mutations at an elevated rate.…”
Section: Restoration Of P53mentioning
confidence: 99%